ANTIDEPRESSANT AND ANXIOLYTIC EFFECTS OF ETHANOL EXTRACTS FROM FOUR PIPER SPECIES - Oesterreich, Silvia Aparecida; Traesel, Giseli Karenina; Piccinelli, Ana Claudia; Aquino, Diana Figueiredo Santana; Mota, Jonas; Estanislau, Celio; Kassuya, Cândida Aparecida Leite (SaBios-Revista de Saúde e Biologia, 2015)
This study objected to assess the pharmacological effects of ethanol extracts from Piper aduncum L. (AD), Piper glabratum (GL) Kunth, Piper amalago (AM) and Piper visosanum Yuncher (VIS) on the CNS in animal models. Therefore, we used a quantitative type research, where the rats were allocated into six experimental groups AD, GL, VIS, AM, NC (negative control) and PC (positive control). Were performed the elevated plus-maze, open-field and forced swimming tests. The extracts were orally administered (300 mg/kg) diary single dose, thirty minutes before testing. A significant increase was observed in locomotors activity and the time spent on the open arms in the AD group, when compared to the NC group, suggesting an anxiolytic effect. VIS group also exhibited a potential anxiolytic effect, since exploratory activity increased significantly relative to the PC group in the open field test. GL, in the forced swim test underwent a significant reduction in the time and frequency of swimming compared to the PC group, which decreases in active behavior, indicating a possible depressive effect. AD demonstrated antidepressant effects in the forced swimming test when compared to the PC. AM significantly increased the activity of self-cleaning when compared to the NC group, reinforcing the possible anxiogenic effect of the species. EFEITOS ANTIDEPRESSIVOS E ANSIOLÍTICOS DO EXTRATO ETANÓLICO DE QUATRO ESPÉCIES DE PIPER Este estudo teve por objetivo avaliar os efeitos farmacológicos do extrato etanólico de Piper aduncum L. (AD), Piper glabratum (GL) Kunth, Piper amalago (AM) e Piper visosanum Yuncher (VIS) no SNC em modelos animais. Para tanto, utilizou-se de uma pesquisa tipo quantitativa, aonde os ratos foram alocados em seis grupos experimentais AD, GL, AM, VIS, NC (controle negativo) e PC (controle positivo). Foram realizados os testes de labirinto em cruz elevado, campo aberto e natação forçada. Os extratos foram administrados via oral (300 mg/kg) em uma única dose diária, 30 minutos antes dos testes. Um aumento significativo foi observado na atividade locomotora e o tempo gasto nos braços abertos no grupo AD, em comparação com o grupo NC, sugerindo efeito ansiolítico. O grupo VIS também exibiu potencial efeito ansiolítico, uma vez que a atividade exploratória aumentou significativamente em relação ao grupo PC no teste do campo aberto. GL, no teste de natação forçada, apresentou redução significativa no tempo e frequência de nado em comparação do grupo PC, que diminuiu seu comportamento ativo, indicando possível efeito depressivo. AD demonstrou efeito antidepressivo no teste de natação forçada quando comparado ao PC. AM aumentou significativamente a atividade de auto limpeza, quando comparado ao grupo NC, reforçando o possível efeito ansiogênico da espécie.